DNA Ploidy and S-Phase Fraction in Carcinoma of the Gallbladder Related to Histopathology, Number of Gallstones and Survival 1 - Ulf Gustafsson; Curt Einarsson; Lennart C. Eriksson; Virgil Gadaleanu; Staffan Sahlin; Bernhard Tribukait (Analytical Cellular Pathology)
Gallstones are a risk factor for the development of gallbladder cancer. We studied DNA ploidy and cell cycle composition by flow cytometry in archival specimens from 52 gall bladder carcinomas in relation to histopathological grade, tumour stage, gallstone number and survival. 69% of the gallbladder carcinomas showed aneuploidy. All tumours with single stones (N=11) were aneuploid while only 61% of tumours with multiple stones (N=41) were aneuploid (p=0.002). DNA aneuploidy was related to increase in T‐category (p=0.01), grade (p=0.02), and nuclear pleomorphism (p=0.0005). The distribution of DNA ploidy shifted from tetraploid in low stage towards triploid positions in high stage tumours (p=0.02) combined with higher S‐phase values in triploid tumours (p=0.05). S‐phase fraction increased during development from normal tissue to dysplasia, cancer in situ and cancer in diploid cases (p=0.0002), and further at the change from diploid to aneuploid (p=0.004). At a median cancer specific survival time of four months patients with diploid tumours had a better survival than those with aneuploid tumours (p=0.02). In multivariate analysis of the tumour characteristic, only T‐category and tumour grade were independent prognostic factors. The shift from diploid to aneuploid and the further shift of ploidy within aneuploid tumours are in agreement with the concept of a clonal development of gallbladder cancer. These changes are combined with a stepwise increase in the fraction of S‐phase cells. Low frequency of symptoms in single stone patients may be the reason for detection of malignancy at a late stage of tumour development.